Study Protocol of a School-Based Randomized Controlled Trial to Promote Cycling to School Among Students in Germany Using Intervention Mapping: The ACTS Project - Schönbach, Dorothea M. I.; Chillón, Palma; Marques, Adilson; Peralta, Miguel; Demetriou, Yolanda (Frontiers in Public Health, 2021)
Background: Despite a high rate of bicycle ownership, the prevalence of cycling to school among children and adolescents in Germany has been constantly low. Cycling to school can contribute to meeting the physical activity recommendations, which the majority of children and adolescents in Germany do not meet. Methods: By using intervention mapping, this study protocol describes the systematic planning process of a school-based intervention in Germany aimed to increase the number of days on which students cycle to school and to increase their physical activity levels. To make sure that the intervention will match the needs of students, we conducted a concept mapping study investigating what students need to cycle to school, perceived by students, parents, and teachers. The logic model of change was based on an integration of the self-determination theory and the social-ecological model. We structured our intervention in two phases, a preparatory phase with weekly components for and a practical phase with a daily repeated component of the targeted behavior. In the eight-week preparatory phase, teachers, parents, and peers will be involved. The content of the twelve-week practical phase will involve peers only and was considered as promising based on the findings from a systematic review that we conducted to identify effective strategies of school-based interventions to promote cycling to school among children and adolescents. Overall, our intervention includes 27 behavior change techniques. A researcher, student assistants, teachers, and other collaborators will implement the intervention; a whole-of-school approach with components performed before, during, and after school was chosen. As study design, we decided to draft a two-arm three-level cluster randomized controlled trial. Both the effect and process evaluation were prepared. In the first instance, approximately 250 students aged 12 to 15 from grade 7 or 8, who attend a secondary school of intermediate or high educational level located in (sub)urban regions in Southern Germany, will pilot the intervention. Discussion: We expect to provide an effective and sustainable intervention for students, which gives insights into the mechanisms of change concerning the behavior of cycling to school and its influence on physical activity levels.